IMPROVING THE USE OF VIRTUAL LAN (VLAN) TECHNOLOGY (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article discusses the features of VLAN and its use today, theoretical research on the prospects of using this technology, and the author's conclusions are given.